2023
DOI: 10.3389/fimmu.2023.1208788
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD137 (4-1BB) towards improved safety and efficacy for cancer immunotherapy

Abstract: T cells play a critical role in antitumor immunity, where T cell activation is regulated by both inhibitory and costimulatory receptor signaling that fine-tune T cell activity during different stages of T cell immune responses. Currently, cancer immunotherapy by targeting inhibitory receptors such as CTLA-4 and PD-1/L1, and their combination by antagonist antibodies, has been well established. However, developing agonist antibodies that target costimulatory receptors such as CD28 and CD137/4-1BB has faced cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Based on the X-ray crystal structure, ADG106 bound to a unique epitope at the junction of CRD2 and CRD3 on CD137, which overlapped with the CD137L binding site and was different from the epitopes of two other clinical anti-CD137 agonists, urelumab and utomilumab. 18 Further assessment by a protein-protein interaction enzyme-linked immunosorbent assay revealed that ADG106 competes for binding with the human CD137 ligand to human CD137, displaying an IC 50 value of 5.7 nM ( Figure 1 A).
Figure 1 ADG106 exhibited its ability to bind activated CD4/CD8 + T cells, to activate NF-κB signaling, and to enhance T cell activation (A) ADG106 blocks interactions between CD137 and its ligand in a concentration-dependent manner.
…”
Section: Resultsmentioning
confidence: 99%
“…Based on the X-ray crystal structure, ADG106 bound to a unique epitope at the junction of CRD2 and CRD3 on CD137, which overlapped with the CD137L binding site and was different from the epitopes of two other clinical anti-CD137 agonists, urelumab and utomilumab. 18 Further assessment by a protein-protein interaction enzyme-linked immunosorbent assay revealed that ADG106 competes for binding with the human CD137 ligand to human CD137, displaying an IC 50 value of 5.7 nM ( Figure 1 A).
Figure 1 ADG106 exhibited its ability to bind activated CD4/CD8 + T cells, to activate NF-κB signaling, and to enhance T cell activation (A) ADG106 blocks interactions between CD137 and its ligand in a concentration-dependent manner.
…”
Section: Resultsmentioning
confidence: 99%